Resposta :
OLÁ
[tex]3r - 6 = 6r + 21r \\ 3r - 6 = 27r \\ 3r = 27r + 6 \\ 3r - 27r = 6 \\ - 24r = 6 \\ r = \frac{ 6}{ - 24} \\ simplifique \: por \: 6 \\ r = - \frac{1}{4} \\ espero \: ter \: ajudado[/tex]
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/d1f/15c159d3297effd8b577afc139852eca.jpg)
OLÁ
[tex]3r - 6 = 6r + 21r \\ 3r - 6 = 27r \\ 3r = 27r + 6 \\ 3r - 27r = 6 \\ - 24r = 6 \\ r = \frac{ 6}{ - 24} \\ simplifique \: por \: 6 \\ r = - \frac{1}{4} \\ espero \: ter \: ajudado[/tex]